Recognition and Justice in Paul Ricoeur’s ethics - Obregón Cabrera, José Luis (2017)
This article aims to show that the recognition and justice are fundamental principles in the ethics of Paul Ricoeur who presents in his book Oneself as another. On the one hand, it is to examine the concept of identity in the hermeneutics of Ricoeur and the role of otherness in the constitution of the identity of the subject as oneself. And secondly, we analyze the central concepts of ethics Ricoeur whose philosophical argument will be developed in three stages. This argumentative way achieve integrate two ethical paradigms (teleological ethics and deontological ethics), and allow us to describe their ethics based on three themes: the priority of recognition in the ethics of Ricoeur, the meanings of the notion of recognition and justice as aim of ethics, which in turn is mediated by creating universal in context. Through this analysis, we show that justice is conditioned by the recognition of the other and dialogue in its ethical proposal.